Free Energy Perturbation Calculations of the Thermodynamics of Protein Side-Chain Mutations. Issue 7 (7th April 2017) - Steinbrecher, Thomas; Abel, Robert; Clark, Anthony; Friesner, Richard
Abstract: Protein side-chain mutation is fundamental both to natural evolutionary processes and to the engineering of protein therapeutics, which constitute an increasing fraction of important medications. Molecular simulation enables the prediction of the effects of mutation on properties such as binding affinity, secondary and tertiary structure, conformational dynamics, and thermal stability. A number of widely differing approaches have been applied to these predictions, including sequence-based algorithms, knowledge-based potential functions, and all-atom molecular mechanics calculations. Free energy perturbation theory, employing all-atom and explicit-solvent molecular dynamics simulations, is a rigorous physics-based approach for calculating thermodynamic effects of, for example, protein side-chain mutations. Over the past several years, we have initiated an investigation of the ability of our most recent free energy perturbation methodology to model the thermodynamics of protein mutation for two specific problems: protein–protein binding affinities and protein thermal stability. We highlight recent advances in the field and outline current and future challenges. Graphical Abstract: Highlights: An overview of the field of protein free energy calculations Recent advances in predicting mutation effects on protein stability and antibody–antigen binding affinity are highlighted. Successes and challenges in using rigorous physics-based models to predict protein structure and energetics are discussed. Outlook on the expected future of the protein free energy calculation field